The Comparison of The Phonological Features of Sikka Language and English - Darmawan Darmawan; Gunawan Suryoputro (Journal of ELT Research: The Academic Journal of Studies in English Language Teaching and Learning, 2019)
The paper is aimed to find out: (1) the similarities and the differences of segmental features of Sikka language and English, and (2) the appropriate way to solve the problem of phonological teaching in Maumere. The data was collected from EFL participants who were their mother tongue are Sikka language, one of local languages in Maumere East Nusatenggara Island, Indonesia. To collect the data, theAural Phoneme Discrimination test, the Phoneme Recognition tes, andReading test were used. The findings revealed that errors were largely limited to final stops and sibilants, initial and final affricates, and interdentals. The error data did not completely accord with previous findings. A language transfer viewpoint offers an explanation as to why these particular sounds were found difficult for the participants. Patterns in the error data showed that stops were mostly devoiced, and these processes were developmental. The affricates and interdentals were frequently generalized to a stop or sibilant found in the first language. Overgeneralization of these articulatory difficult sounds is a common developmental process. Both transfer and developmental factors and their interaction explain much of the error data, though other factors such as hypercorrection and spelling interference also seem to play a role. An implication of the study is that these systematic, specific errors, dependent on first language, should be taken into account when teaching pronunciation to English learners from these local language groups. Keywords: Contrastive analysis, phonetic features, Sikka language